The Role of Corporate Governance in Preventing Business Crime in ASEAN Public Companies - Ainun Nur Fadilah; Andri Hayu Kirani (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the role of corporate governance in preventing business crime in Indonesian public companies, comparing it with corporate governance practices in Malaysia and Thailand as regional benchmarks. Research Design & Methods: This study uses a qualitative approach with a systematic literature review method of regulatory documents, international agency reports, and academic studies related to corporate governance and corruption in the ASEAN region. The focus of the study is on three pillars of governance: shareholder rights, board structure, and external control mechanisms such as accounting and auditing standards. Findings: The study shows that Indonesia still faces major challenges in effectively implementing corporate governance principles, particularly in terms of transparency, protection of minority shareholders, and oversight of related-party transactions. Indonesia's score on the ASEAN Corporate Governance Scorecard and corruption perception index is low compared to Malaysia and Thailand. Implications & Recommendations: Institutional reforms are needed, including strengthening oversight functions, compliance reporting requirements, restrictions on directors' terms of office, and protection for whistleblowers. Indonesia could also adopt the comply or explain principle, which has been successfully implemented in Malaysia and Thailand, to improve accountability and transparency.Contribution & Value Added: This study makes an important contribution to filling the gap in the literature on the relationship between corporate governance and business crime in developing countries, and offers a relevant regional perspective for formulating policies based on institutional comparisons.